Implementasi Manajemen Resiko Bank Syariah - Tsamara Balqis; Syafrina Yuni Lubis; Sugianto (Rayah Al-Islam, 2023)
Every business activity is inseparable from risks that can disrupt business continuity, including sharia banking business activities. The characteristics of products and services in Islamic banking require identification, measurement, monitoring and risk management functions in accordance with these activities. Islamic banks always face different types of risks with various complexities inherent in their business activities.activities. Therefore, implementing risk management in Islamic Banking is one of the very important things to implement to identify, measure and control the various risks that will be faced. Through this article, we discuss the implementation of Islamic bank risk management. In this journal, we also discuss risk classification in Islamic banks as well.